Modeling the Price of Emergency Power Transmission Lines in the Reserve Market Due to the Influence of Renewable Energies - Iranmehr, Hamid; Aazami, Rahmat; Tavoosi, Jafar; Shirkhani, Mohammadamin; Azizi, Amir-Reza; Mohammadzadeh, Ardashir; Mosavi, Amir H.; Guo, Wei (Frontiers in Energy Research, 2022)
The law of free access to the transmission network obliges the transmission network to be in orbit, and on the other hand, the high loads in the transmission network and economic uncertainties cause that the owners of transmission companies, don't have sufficient motivation and resources to rebuild and develop the network. This paper presents a method for calculating the reference price that a transmission line owner uses to bid on a price in excess of the nominal capacity of the transmission line under his ownership. For this purpose, first, the effects of operating a transmission line at a power greater than the rated power are described. After that, the reduction rate of the transmission line due to operation in these conditions is calculated, and finally the price determination is calculated based on the reduction rate of the generated life. In the next stage, this excess capacity is entered the two-stage model of energy market and reservation considering renewable energy sources as a price offer function. Numerical results of 6Shin network show that the entry of renewable energy sources reduces energy costs, but the costs of the reservation market increases due to uncertainty, but despite the emergency capacity, these costs are reduced due to the use of cheap resources in the network.